THE PLACE AND ROLE OF COUNTRY STUDIES TEXTS IN KOREAN LANGUAGE EDUCATION - Erkinov Ahrorbek (International Scientific and Current Research Conferences, 2025)
The article examines the importance of country studies texts in the methodology of teaching Korean as a foreign language. The role of the linguocultural component in the formation of students' communicative competence is analyzed. The author studies the theoretical foundations of linguistic country studies in the context of the Korean language and provides practical recommendations for integrating country studies materials into the educational process.